Effect of impurities on ultra-pure hydrogen production by pressure vacuum swing adsorption - Golmakani, Ayub; Nabavi, Seyed Ali; Manovic, Vasilije (Elsevier, 2019)
The most viable technology for production of ultra-pure hydrogen (>99.99%), required for fuel cells, is steam methane reforming (SMR) coupled with pressure vacuum swing adsorption (PVSA). A PVSA process with a two-layer bed of activated carbon (AC)/zeolite 5A for ultra-pure hydrogen production from syngas was developed and simulated with the aim of exploring the effect of impurities on energy intensity of the process. The simulated concentration profiles showed that CH4 was removed by first half of the AC layer, CO2 and CO were mostly removed by the end of that layer, but zeolite 5A (the second layer) could not completely remove the remaining N2. Further, the effect of the N2 on performance of the PVSA process was demonstrated by simulating purification of two feeds with 3.1 and 1.1 vol% N2, respectively. The 2% drop in N2 concentration in the syngas feed resulted in decreased energy consumption of the PVSA process from 940 kJ/kg to 430 kJ/kg H2, while H2 recovery increased from 47% to 55%. Therefore, the presence of N2 has a very large impact on recovery and energy intensity of the ultra-pure hydrogen production process, and development of adsorbents with better N2 removal performances is required.
Keywords: syngas impurities; pressure vacuum swing adsorption; fuel cell specifications; cyclic adsorption process; hydrogen production